Analysis of the Role of Social Entrepreneurship in Achieving the Sustainable Development Goals (SDGS) in Indonesia - Eni Susilowati; Andi Basuki; Choiru Umatin (Formosa Journal of Multidisciplinary Research, 2024)
This research focuses on the role of social entrepreneurship in achieving the Sustainable Development Goals (SDGs) in Indonesia. Indonesia faces social, economic, and environmental challenges that require innovative and sustainable approaches. Social entrepreneurship, with a progressive focus on creating positive social and environmental impacts, offers a potential path to facilitate progress. This qualitative research assesses the impacts, challenges, and supporting factors of social entrepreneurship in Indonesia, as well as its alignment with certain SDGs, tangible contributions, motivations, and challenges faced by social entrepreneurs. The importance of a supportive ecosystem, diverse funding sources, and supportive policies is emphasized to harness the full potential of social entrepreneurship in driving sustainable development.